Origin and molecular organization of supernumerary chromosomes of Prochilodus lineatus (Characiformes, Prochilodontidae) obtained by DNA probes - Voltolin, Tatiana Aparecida [UNESP]; Laudicina, Alejandro; Senhorini, Jose Augusto; Bortolozzi, Jehud [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Springer, 2010)
In Prochilodus lineatus B-chromosomes are visualized as reduced size extra elements identified as microchromosomes and are variable in morphology and number. We describe the specific total probe (B-chromosome probe) in P. lineatus obtained by chromosome microdissection and a whole genomic probe (genomic probe) from an individual without B-chromosome. The specific B-chromosome was scraped and processed to obtain DNA with amplification by DOP-PCR, and so did the genomic probe DNA. Fluorescence in situ hybridization using the B-chromosome probe labeled with dUTP-Tetramethyl-rhodamine and the genomic probe labeled with digoxigenin-FITC permitted to establish that in this species supernumerary chromosomes with varying number and morphology had different structure of chromatin when compared to that of the regular chromosomes or A complement, since only these extra elements were labeled in the metaphases. The present findings suggest that modifications in the chromatin structure of B-chromosomes to differentiate them from the A chromosomes could occur along their dispersion in the individuals of the population.
Keywords: B-chromosome; Origin; Evolution; Molecular organization; Probes